PERAN LEVERAGE SEBAGAI PEMEDIASI PENGARUH KARAKTER EKSEKUTIF, KOMPENSASI EKSEKUTIF, CAPITAL INTENSITY, DAN SALES GROWTH TERHADAP TAX AVOIDANCE - Moehammad Iman Nugraha; Susi Dwi Mulyani (Jurnal Akuntansi Trisakti, 2019)
The purpose of this research is to examine the effect of executive character, executive compensation, capital intensity, and sales growth on tax avoidance with leverage as intervening variable. This research is using samples of manufacture companies listed in Indonesia Stock Exchange during the period of 2014-2017. This research uses a purposive sampling to gather and sort data. The sample being fulfilled in this research are 43 companies with 4 (four) years observation. The hypothesis would be analysed using multiple linear regression and path analysis.The data analysing show that executive character has no effect on leverage. Executive compensasion has positive effect on leverage. Capital intensity has positive effect on leverage. Sales growth has positive effect on leverage. Leverage has positive effect on tax avoidance. Executive character has positive effect on tax avoidance. Executive compensasion has positive effect on tax avoidance. Capital intensity has positive effect on tax avoidance. Sales growth has positive effect on tax avoidance. Leverage able to mediate the effect of executive compensasion on tax avoidance, but Leverage is not able to mediate the effect of executive character capital, intensity on tax avoidance, and sales growth on tax avoidance.